Comparison of Bioimpedance and Underwater Weighing Body Fat Percentage Before and Acutely After Exercise at Varying Intensities. Issue 5 (May 2017) - Nickerson, Brett S.; Esco, Michael R.; Kliszczewicz, Brian M.; Freeborn, Todd J.
Abstract : Abstract: Nickerson, BS, Esco, MR, Kliszczewicz, BM, and Freeborn, TJ. Comparison of bioimpedance and underwater weighing body fat percentage before and acutely after exercise at varying intensities. J Strength Cond Res 31(5): 1395–1402, 2017—The purpose of this study was to compare single-frequency bioelectrical impedance analysis (BIA) and bioimpedance spectroscopy (BIS) with underwater weighing (UWW) body fat percentage (BF%) before (PRE), immediately post (IP), and 60 minutes post (60P) an acute bout of moderate and vigorous aerobic exercise. Nine men (age = 24.6 ± 3.7 years) volunteered for this study. Subjects visited the laboratory on 3 separate occasions. Testing included two 30-minute exercise sessions at 60 and 80% heart rate reserve (HRR) and a 30-minute control (CON) trial. The constant error (CE) was significantly higher for BIA at each time point and exercise session (CE = 3.0–4.9% for 60% HRR; 2.5–4.7% for 80% HRR). Conversely, BIS yielded a nonsignificant CE at each time point and exercise session (CE = −0.9 to 1.1% for 60% HRR; −0.3 to 1.2% for 80% HRR). The standard error of estimate ( SEE ) for both exercise sessions ranged from 2.7 to 3.1% and 3.8–4.3% for BIA and BIS, respectively. The 95% limits of agreement were narrower for BIA (60% HRR = ±5.5 to 7.8%; 80% HRR = ±6.6 to 8.5%) than BIS (60% HRR = ±8.4 to 9.4%; 80% HRR = ±8.1 to 10.2%). Results indicate that BIS can be used for mean group BF% in men at PRE, IP, and 60P time periods. However, BIA yielded a lower SEE and 95% limits of agreement than BIS. Therefore, BIA provides better individual estimates of BF% in men, but the CE should be taken into consideration.